Effect of caffeine on attack decision-making in trained beach volleyball players following prolonged cognitive effort induced by social media use: a randomized, single-blind, crossover pilot study - Yago P. Costa; Bianca Stefanny Lopes-da-Silva; Fabiano S. Fonseca; Maicon Albuquerque; Gilmário R. Batista; Leonardo S. Fortes (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Mental fatigue is a psychobiological state characterized by a feeling of tiredness or lack of energy after performing cognitive activities. Recently, studies have found that prolonged use of social media can cause mental fatigue and consequently impair decision-making performance in athletes. On the other hand, caffeine may counteract mental fatigue by antagonizing adenosine. Therefore, this study aimed to analyze the effect of caffeine on the attack decision-making skill of trained beach volleyball players after prolonged cognitive effort by using social media on smartphones. Methods Twelve trained young male beach volleyball players (Agemean: 18.38 ± 1.49 years old; Heightmean: 179.83 ± 7.54 cm; Body massmean: 73.14 ± 16.42 Kg) were recruited to a randomized, single-blind, crossover pilot study. Participants performed a beach volleyball task on low-dose caffeine (CAF: 3 mg/kg) or placebo (PLAC: crystallized cellulose) conditions after cognitive effort by social media use. In both conditions, participants used social media for 30 min and took capsules (CAF or PLAC, without identifying the type of capsule) 60 min before the beach volleyball task. Mental fatigue was assessed by visual analog scale and executive function by Stroop task (accuracy and response time). The Game Performance Assessment Instrument (GPAI) was used to assess attack decision-making skills through video recordings. Results The subjective perception of mental fatigue increased only in the CAF condition (p = 0.018), and Stroop task performance was not different for all variables analyzed in both conditions (p > 0.05). Finally, the decision-making skill was not different between situations in attack (p = 0.890; d = 0.054) or counterattack (p = 0.617; d = 0.141). Conclusions At similar levels of mental fatigue, low-dose caffeine was not superior to placebo in improving attack decision-making. Considering the limitations of time and sample size, the results must be interpreted with caution. Trial registration number Brazilian Clinical Trial Register (RBR-2yyd8jb). Registered 01 January 2024 (Retrospectively registered).